Response and Outcome of Moderate Dose Adrenocorticotropic Hormone in the Treatment of West Syndrome (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: West Syndrome (WS) consist of a triad of epileptic spasms, hypsarrhythmia on EEG and arrest or regression of psychomotor development. Although ACTH has been found to be effective in the treatment of WS, questions remain regarding the optimum dosage, type of ACTH, duration of therapy, and its comparative efficacy with other treatment options.Objective: To assess the response and outcome of treatment with moderate dose (100 IU/m2) ACTH in children of west syndrome.Methodology: This was a prospective observational study and done over 1-year period (July 2017 to June 2018) in Pediatric Neurology OPD, National Institute of Neuroscience and Hospital (NINS&H), Dhaka among the patients with West syndrome. All study participants were treated with moderate dose ACTH (100 unit/m2) (I/M) and treatment completed within 12 weeks. Patients were followed up at 2, 4, 6 and 12 WKs of treatment.Results: Total 52 cases were for enrolled. In this study it was found that complete cessation of spasm 21/50 (42%), ≥50% reduction of spasm 12/50 (24%),